Pets of Konrad Lorenz. Theorizing in the social world of pet owners - Konecki, Krzysztof T. (Qualitative Sociology Review, 2007)
This article explores the personal account titled Man meets dog ([1949] 2002) by an outstanding ethologist Konrad Lorenz who is one of the key theoreticians of the social world of pet owners. His lines of argumentation and categories of pet perception within this social world may be reconstructed from his personal recollections. The concepts of the social world and arena are the key notions that integrate the current analysis. The arena is also formed in the course of the inner conversation and is often going together with the outer disputes of a social world . It might seem that Konrad Lorenz as a scientist and ethologist should avoid using anthropomorphic categories. However, as he shares the same space (including private space) and communicates with domestic animals, the author tends to anthropomorphise their behaviour, even though formally he opposes or even despises the idea, applying a disdainful term of “sentimental anthropomorphisation” to people who do so. Additionally, the article addresses the biographic context of the ethologist’s life and his writings together with the activities of the Second World War as well as his collaboration with the Nazi government. Konrad Lorenz represents the socalled “cult of nature” approach which, in the opinion of his opponents, has a lot in common with the Nazi doctrine (Sax 1997).